Lithium ion battery pole piece and preparation method thereof

By adopting a three-layer composite edge coating structure on the positive electrode of the lithium-ion battery, the single-layer coating is easily broken down, limited mechanical strength, poor chemical corrosion resistance and serious material disconnection under high voltage and high temperature environments, and higher insulation performance, mechanical strength, chemical corrosion resistance and thermal stability are achieved, improving the safety performance and yield of the battery.

CN119560507APending Publication Date: 2025-03-04JIANGXI GANFENG BATTERY TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411723924.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode edge treatment technology has problems such as single-layer coatings that are prone to breakdown under high voltage and high temperature environments, limited mechanical strength, poor chemical corrosion resistance and serious material disconnection, resulting in reduced battery performance and safety hazards.

Method used

The three-layer composite edge coating structure is adopted, including the base bonding layer, the intermediate functional layer and the surface protective layer. By rationally designing the materials of each layer, the insulation performance, mechanical strength, chemical corrosion resistance and thermal stability are improved.

Benefits of technology

Effectively prevent the current collector from burrs during laser cutting, increase the internal resistance of the battery at high temperature, improve safety performance, prevent material bleeding, and improve yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560507A_ABST
    Figure CN119560507A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery pole piece and a preparation method thereof, and the preparation method comprises the following steps: coating two sides of at least one surface of a current collector with bottom layer slurry, and drying to prepare the current collector containing a bottom layer edge coating; coating the bottom edge coating with the intermediate layer slurry, and drying to obtain a current collector containing an intermediate edge coating; coating the surface layer slurry on the surface of the middle edge coating, and drying to prepare a composite current collector containing the surface layer edge coating; coating an uncoated area on the surface of the composite current collector with positive electrode active material slurry to prepare the positive electrode plate; the bonding layer in the composite edge coating is used for ensuring tight combination of the coating and the current collector and improving the peeling strength and durability of the coating; the function layer is used for providing main insulation performance, mechanical strength and chemical corrosion resistance; the protection layer is used for providing additional chemical corrosion resistance and thermal stability and protecting the internal structure from being corroded by electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a lithium ion battery pole piece and a preparation method thereof. Background Art

[0002] With the development of new energy, the requirements for energy density of existing batteries are further improved. New energy power batteries are usually secondary batteries. Secondary batteries are also called rechargeable batteries or storage batteries. They refer to batteries that can be recharged to activate active materials after being discharged and continue to be used.

[0003] Lithium-ion battery pole pieces are mainly composed of active materials, conductive agents, binders, and current collectors. Among them, aluminum foil or carbon-coated aluminum foil is generally used as the current collector for the positive electrode, and copper foil is used as the current collector for the negative electrode. In the manufacturing process of lithium-ion batteries, the edge of the positive pole piece is prone to burrs, physical damage or contamination when the laser cutting of the pole ear, resulting in direct contact between the positive and negative poles or indirect contact through tiny metal particles and other foreign objects, thereby resulting in yield or even internal short circuit, causing battery performance to decline, and may also cause thermal runaway and fire accidents, posing a serious threat to the safety of users' lives and property. Therefore, in the production of lithium-ion battery pole pieces, the edge processing of the positive pole piece is crucial. At present, the edge processing technology of the positive pole piece of lithium-ion batteries mainly focuses on adding a coating layer to the edge of the pole piece. The coating is usually composed of inorganic materials, which aims to improve the insulation performance and mechanical strength of the pole piece and reduce the risk of burrs and short circuits.

[0004] Although the current edge coating technology has improved the safety of batteries to a certain extent, there are still some problems:

[0005] 1. Single-layer coatings are prone to breakdown under high voltage and high temperature environments. Especially in high-energy density batteries, the voltage window of the positive electrode material is higher, which places higher requirements on the insulation performance of the coating. The insulation performance of existing single-layer coatings is difficult to meet these stringent conditions, resulting in an increased risk of short circuits;

[0006] 2. The mechanical strength of the single-layer edge coating is still limited and it is easy to peel off or crack;

[0007] 3. The chemical corrosion resistance of the single-layer edge coating is poor and it is easy to peel off after long-term use;

[0008] 4. At present, the edge coating adopts the method of coating the edge coating slurry and the positive electrode active material at the same time, which is easy to cause material cross-coating. Therefore, we propose a lithium ion battery pole piece and its preparation method to solve the above problems. Summary of the invention

[0009] The purpose of the present invention is to solve the shortcomings existing in the prior art. In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0010] A method for preparing a lithium-ion battery electrode, comprising the following steps:

[0011] Step 1: coating the bottom layer slurry on both sides of at least one surface of the current collector, and drying to obtain a current collector containing a bottom layer side coating;

[0012] Step 2: coating the intermediate layer slurry on the bottom edge coating layer, drying, and obtaining a current collector containing the intermediate edge coating layer;

[0013] Step 3: coating the surface slurry on the surface of the middle edge coating layer, drying, and obtaining a composite current collector containing the surface edge coating layer;

[0014] Step 4: coating the positive electrode active material slurry on the uncoated area of ​​the surface of the composite current collector to obtain the positive electrode sheet.

[0015] Further preferably, the bottom layer slurry comprises 5% to 50% of a bottom layer binder and 50 to 95% of deionized water, and the bottom layer binder comprises one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyacrylic acid, polyvinyl alcohol, and polyacrylate.

[0016] Further preferably, the intermediate layer slurry includes 1 to 30% of an inorganic filler, 1 to 30% of an intermediate layer binder and 40 to 98% of N-methylpyrrolidone or deionized water, and the inorganic filler includes one or more of boehmite, aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium carbonate, magnesium carbonate, graphene oxide, boron nitride, montmorillonite and spinel.

[0017] Further preferably, the surface slurry comprises 2-30% of resin and 70-98% of N-methylpyrrolidone or deionized water, and the resin comprises one or more of epoxy resin, polyurethane resin, phenolic resin, acrylic resin, polyvinyl chloride, silicone resin, and urea-formaldehyde resin.

[0018] More preferably, the thickness of the composite current collector is 1 μm to 60 μm, and the width of the composite current collector is 0.1 mm to 2 mm.

[0019] More preferably, the particle size of the inorganic filler is 100 to 3000 nm.

[0020] Further preferably, the solid content of the intermediate layer slurry is 10 wt% to 50 wt%.

[0021] Further preferably, the intermediate layer adhesive includes one or more of polymethacrylic acid adhesive, polyacrylonitrile adhesive, polyacrylamide adhesive, polymethyl methacrylate adhesive, polyacrylate adhesive, polyvinyl alcohol adhesive, styrene-butadiene rubber adhesive, and polyvinylidene fluoride adhesive.

[0022] More preferably, the bottom edge coating, the middle edge coating and the surface edge coating have a thickness of 0.5 to 40 μm, a width of 0.1 mm to 2 mm, and a density of 0.5 to 35 g / m2.

[0023] More preferably, the viscosity of the bottom layer slurry and the middle layer slurry are both 500-4000 cp, and the viscosity of the surface layer slurry is 300-3000 cp.

[0024] A lithium-ion battery pole piece is prepared by the method described above.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The edge coating of the present invention has a three-layer composite structure, wherein the bottom layer is a bonding layer, which ensures that the coating is closely bonded to the current collector and improves the finishing adhesion and durability of the edge coating; the middle layer is a functional layer, which provides the main insulation performance, mechanical strength and chemical corrosion resistance; the surface layer is a protective layer, which provides additional chemical corrosion resistance and thermal stability, and protects the inside of the edge coating from being corroded by the electrolyte; the present invention improves the insulation performance, mechanical strength, chemical corrosion resistance and thermal stability of the coating comprehensively by rationally designing the materials of each layer compared with the traditional single-layer edge coating;

[0027] The composite edge coating can effectively prevent the current collector from generating burrs during the laser cutting process. When the battery cell is overcharged or impacted, causing the internal temperature of the battery to rise, the edge coating can increase the internal resistance of the battery at high temperature, play an insulating role, and improve safety performance.

[0028] The composite edge coating layer is coated separately from the positive electrode active material, which effectively prevents the phenomenon of material leakage during the edge coating process and improves the yield rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a flow chart of the preparation method of the present invention;

[0030] Figure 2 is a top view of the positive electrode;

[0031] Figure 3 This is the front view of the positive electrode.

[0032] In the figure: current collector 1, composite side coating 2, positive electrode material layer 3, bottom side coating 4, middle side coating 5, surface side coating 6. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0034] Reference Figure 1-Figure 3 , a lithium-ion battery pole piece and a preparation method thereof, the steps are as follows:

[0035] Step 1: coating the bottom layer slurry on both sides of at least one surface of the current collector 1, and drying, to obtain the current collector 1 containing the bottom layer side coating;

[0036] A certain amount of bottom layer binder and a certain amount of deionized water are mixed and stirred to obtain the bottom layer slurry of the composite edge coating layer 2; the proportion of the bottom layer binder is 5% to 50%, and the proportion of the deionized water is 50 to 95%; the bottom layer binder includes one or more of sodium carboxymethyl cellulose (CMC), hydroxypropyl methyl cellulose (HPMC), polyacrylic acid (PA), polyvinyl alcohol (PVA), and polyacrylate (PMA); the viscosity of the bottom layer slurry of the composite edge coating layer 2 is 500 to 4000cp.

[0037] In the embodiment, the binder is sodium carboxymethyl cellulose, the ratio of sodium carboxymethyl cellulose is 50%, the ratio of deionized water is 50%, the stirring time is 0.5 to 2 hours, and the bottom slurry of the composite edge coating 2 is prepared. The slurry is applied on the current collector 1 by spraying or roller coating, and then dried and solidified to obtain a pole piece containing the bottom edge coating.

[0038] In the embodiment, the drying and curing method is baking, the baking temperature is 50-100° C., and the baking time is 20-150 min.

[0039] The bottom layer of the composite edge coating 2 can improve the bonding effect between the composite edge coating 2 and the current collector 1 , making the edge coating less likely to fall off or shed powder, thereby improving the stability of the connection between the edge coating and the current collector 1 .

[0040] Step 2: coating the intermediate layer slurry on the bottom edge coating layer, and drying, to obtain a current collector 1 containing the intermediate edge coating layer;

[0041] N-methylpyrrolidone or deionized water is first mixed with a certain amount of inorganic filler, and then an intermediate layer binder is added for second mixing to obtain the intermediate layer slurry; the ratio of the inorganic filler, the intermediate layer binder, and the N-methylpyrrolidone or deionized water is 1-30%: 1-30%: 40-98%;

[0042] The inorganic filler includes one or more of boehmite (AlOOH), aluminum oxide (Al2O3), silicon oxide (SiO2), titanium oxide (TiO2), zirconium oxide (ZrO2), magnesium oxide (MgO), calcium carbonate (CaCO3), magnesium carbonate (MgCO3), graphene oxide (GO), boron nitride (BN), montmorillonite (MMT), and spinel (MgAl2O4); the particle size of the inorganic filler is 100-3000nm; the intermediate layer binder includes one or more of polymethacrylic acid binder (PMAA), polyacrylonitrile binder (PAN), polyacrylamide binder (PAM), polymethyl methacrylate binder (PMMA), polyacrylate binder (PMA), polyvinyl alcohol binder (PVA), styrene-butadiene rubber binder (SBR), and polyvinylidene fluoride binder (PVDF); the viscosity of the intermediate layer slurry of the composite edge coating 2 is 500-4000cp; preferably, the solid content of the intermediate layer slurry of the composite edge coating 2 is 10wt%-50wt%.

[0043] The mixing method is stirring; more preferably, the stirring method is vacuum stirring.

[0044] In the embodiment: N-methylpyrrolidone or deionized water is first mixed with a certain amount of inorganic filler, wherein the inorganic filler is exemplified by Al2O3, and then an intermediate layer binder is added for second mixing, wherein the intermediate layer binder is exemplified by PVDF, and the intermediate layer slurry is obtained after uniform mixing. The intermediate layer slurry is applied on the bottom edge coating of the above-mentioned current collector 1 by roller coating or spraying. Then, drying and curing are performed to form a stable intermediate layer, and the current collector 1 containing the intermediate edge coating is obtained.

[0045] In the embodiment, the ratio of Al2O3, PVDF, N-methylpyrrolidone or deionized water is 30%:30%:40%; the particle size of the inorganic filler is 1000nm, and the mixing method is stirring; further, the stirring method is vacuum stirring; the drying and curing method is baking, the baking temperature is 50-100°C, and the baking time is 20-150min.

[0046] The middle layer provides the main insulation properties, mechanical strength and chemical resistance.

[0047] Step 3: coating the surface slurry on the surface of the middle edge coating layer, and drying, to obtain a composite current collector 1 containing the surface edge coating layer;

[0048] N-methylpyrrolidone or deionized water is mixed and dispersed with a certain amount of resin to obtain the surface slurry of the composite edge coating 2; the resin includes one or more of epoxy resin (EP), polyurethane resin (PUR), phenolic resin (PF), acrylic resin (AC), polyvinyl chloride (PVC), silicone resin (SR), and urea-formaldehyde resin (UF); the ratio of the resin to N-methylpyrrolidone or deionized water is 2-30%:70-98%; the viscosity of the surface slurry of the composite edge coating 2 is 300-3000cp.

[0049] In the embodiment: N-methylpyrrolidone or deionized water is mixed and dispersed with a certain amount of resin, wherein the resin is epoxy resin for example, and the surface slurry of the composite edge coating 2 is obtained after uniform dispersion; the surface slurry is coated on the middle layer of the current collector 1 by spraying or roller coating, and then dried and cured to form a stable protective layer, thereby obtaining the lithium-ion battery electrode containing the composite edge coating 2.

[0050] The ratio of the resin to N-methylpyrrolidone or deionized water is 30%:70%, the drying and curing method is baking, the baking temperature is 50-100° C., and the baking time is 20-150 minutes.

[0051] The top or protective layer provides additional chemical resistance and thermal stability, protecting the edge coating from electrolyte corrosion.

[0052] Step 4: coating the positive electrode active material slurry on the uncoated area of ​​the surface of the composite current collector 1 to obtain the positive electrode sheet.

[0053] A lithium-ion battery pole piece is prepared by the method described above.

[0054] The positive electrode plate includes a current collector 1, an active material, a conductive agent, a binder, and a composite edge coating 2; the composite edge coating 2 includes three main layers: a bottom layer, an intermediate layer, and a surface layer; the bottom layer is a bonding layer, the intermediate layer is a functional layer, and the surface layer is a protective layer; the composite edge coating 2 is coated on both sides of at least one surface of the current collector 1.

[0055] In the embodiment, a certain amount of lithium iron phosphate, PVDF, conductive carbon black, and N-pyrrolidone are mixed to prepare a positive electrode slurry, and the positive electrode slurry is coated on the surface of the current collector 1 by gravure coating or extrusion coating, adjacent to the composite edge coating 2, and after drying, the lithium-ion battery electrode is obtained.

[0056] The drying method is vacuum drying. More preferably, the drying temperature is 50-100° C. and the drying time is 15-60 seconds.

[0057] The bonding layer in the composite edge coating 2 of the present invention ensures that the coating is tightly bonded to the current collector 1 and improves the peel strength and durability of the coating; the functional layer provides the main insulation properties, mechanical strength and chemical corrosion resistance; the protective layer provides additional chemical corrosion resistance and thermal stability and protects the internal structure from electrolyte corrosion.

[0058] The lithium-ion battery pole piece contains a three-layer composite edge coating 2. Compared with a single-layer edge coating, the composite edge coating 2 significantly improves the insulation performance of the edge coating by rationally designing the materials of each layer, effectively preventing the positive and negative electrodes from short-circuiting. At the same time, the composite edge coating 2 has high hardness and toughness, effectively preventing the current collector 1 from generating burrs during laser cutting, effectively resisting physical damage, and improving the safety performance of the battery. In addition, due to the structure of the protective layer, the edge coating can remain stable for a long time in the electrolyte environment, significantly reducing the probability of powder loss and peeling, and extending the service life of the battery. Finally, the coating process for preparing the composite edge coating 2 is simple and efficient, which meets the needs of large-scale production and ensures the stability and consistency of the coating in actual use.

Claims

1. A method for preparing a lithium-ion battery pole piece, characterized in that: Here are the steps: Step 1: coating the bottom layer slurry on both sides of at least one surface of the current collector, and drying to obtain a current collector containing a bottom layer side coating; Step 2: coating the intermediate layer slurry on the bottom edge coating layer, drying, and obtaining a current collector containing the intermediate edge coating layer; Step 3: coating the surface slurry on the surface of the middle edge coating layer, drying, and obtaining a composite current collector containing the surface edge coating layer; Step 4: coating the positive electrode active material slurry on the uncoated area of ​​the surface of the composite current collector to obtain the positive electrode sheet.

2. The method for preparing a lithium-ion battery pole piece according to claim 1, characterized in that: The bottom layer slurry comprises 5% to 50% of a bottom layer binder and 50 to 95% of deionized water. The bottom layer binder comprises one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, polyacrylic acid, polyvinyl alcohol and polyacrylate.

3. The method for preparing a lithium-ion battery pole piece according to claim 1, characterized in that: The intermediate layer slurry includes 1 to 30% of an inorganic filler, 1 to 30% of an intermediate layer binder and 40 to 98% of N-methylpyrrolidone or deionized water, wherein the inorganic filler includes one or more of boehmite, aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium carbonate, magnesium carbonate, graphene oxide, boron nitride, montmorillonite and spinel.

4. The method for preparing a lithium-ion battery pole piece according to claim 1, characterized in that: The surface slurry includes 2-30% of resin and 70-98% of N-methylpyrrolidone or deionized water, and the resin includes one or more of epoxy resin, polyurethane resin, phenolic resin, acrylic resin, polyvinyl chloride, silicone resin, and urea-formaldehyde resin.

5. The method for preparing a lithium-ion battery pole piece according to claim 1, characterized in that: The thickness of the composite current collector is 1 μm to 60 μm, and the width of the composite current collector is 0.1 mm to 2 mm.

6. The method for preparing a lithium ion battery pole piece according to claim 3, characterized in that: The particle size of the inorganic filler is 100 to 3000 nm.

7. The method for preparing a lithium-ion battery pole piece according to claim 3, characterized in that: The solid content of the intermediate layer slurry is 10 wt% to 50 wt%.

8. The method for preparing a lithium-ion battery pole piece according to claim 3, characterized in that: The intermediate layer adhesive includes one or more of polymethacrylic acid adhesive, polyacrylonitrile adhesive, polyacrylamide adhesive, polymethyl methacrylate adhesive, polyacrylate adhesive, polyvinyl alcohol adhesive, styrene-butadiene rubber adhesive, and polyvinylidene fluoride adhesive.

9. The method for preparing a lithium-ion battery pole piece according to claim 1, characterized in that: The thickness of the bottom layer edge coating, the middle layer edge coating and the surface layer edge coating are all 0.5-40 μm, the width is all 0.1 mm-2 mm, and the density is all 0.5-35 g / m2. It is characterized in that the viscosity of the bottom layer slurry and the middle layer slurry are both 500-4000 cp, and the viscosity of the surface layer slurry is 300-3000 cp.

10. A lithium-ion battery pole piece, characterized in that: The battery pole piece is prepared by the method according to any one of claims 1 to 9.